Global Constitutionalism: History, Theory and Contemporary Challenges - Mattias Kumm (Revista Direito e Práxis, 2022)
Notwithstanding the political origins of constitutionalism in the west and the leading role played by the United States in the creation of the new global order after WWII, this origin of the global constitutional project does not undermine the claims to universality underlying it. After laying out a basic account of some core theoretical premises guiding global constitutionalism, the article presents a series of genealogical reflections, in which the basic project of global constitutionalism is affirmed, even as some of its concrete features and their connection to great power domination - and US domination more specifically - is critically highlighted. It concludes that the core challenge that global constitutionalism faces is not the shift of power away from the west to other geographical areas, such as Asia and South America. Its core challenge are structural inadequacies that are glossed over complacently and self-interestedly by powerful actors claiming to speak in its name and discrediting its basic ideas among those who suffer as a result. – – Apesar das origens políticas do constitucionalismo no Ocidente e o papel de liderança desempenhado pelos Estados Unidos na criaç\~ao da nova ordem global após a Segunda Guerra Mundial, essa origem do projeto constitucional global n\~ao compromete as reivindicaç\~oes de universalidade subjacentes. Depois de expor algumas premissas teóricas fundamentais que norteiam o constitucionalismo global, o artigo apresenta uma série de reflex\~oes genealógicas nas quais o projeto básico do constitucionalismo global se afirma, mesmo que algumas de suas características concretas e sua conex\~ao com a dominaç\~ao das grandes potências – e a dominaç\~ao dos EUA, mais especificamente – seja destacada criticamente. Conclui que o principal desafio que o constitucionalismo global enfrenta n\~ao é a mudança de poder do ocidente para outras áreas geográficas, como Ásia e América do Sul. Seu principal desafio s\~ao as inadequaç\~oes estruturais que s\~ao encobertas com complacência e interesse próprio por atores poderosos que alegam falar em seu nome e desacreditam suas ideias básicas entre aqueles que, como resultado, prejudicam.
Keywords: 330; global constitutionalism; affirmative genealogy; critical genealogy; American empire; constitucionalismo global; genealogia afirmativa; genealogia crítica; império americano